1976
DOI: 10.1097/00000658-197601000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Catheter Placement in the Treatment of Venous Air Embolism

Abstract: Venous air embolism is a potential complication of many surgical, therapeutic, and diagnostic procedures. Aspiration of air via a catheter placed in the superior vena cava or right atrium or placed in the pulmonary outflow tract and pulled through the right heart chambers had been advocated for the treatment of venous air embolism. In this study, three catheter positions were analyzed to determine which was best for removal of gas after induction of massive venous air embolism in dogs. In 18 dogs, 9 of which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…While right ventricular aspiration significantly enhanced air recovery in our study, Sink et al [29] found no differences in air recovery rates via a Swan-Ganz-catheter placed within the pulmonary artery, right ventricle, or right atrium in dogs, possibly due to its small inner diameter. In our study, aspiration catheters had similar and high flow rates, approximately 10 times greater than that of a pulmonary artery catheter.…”
Section: Discussioncontrasting
confidence: 75%
“…While right ventricular aspiration significantly enhanced air recovery in our study, Sink et al [29] found no differences in air recovery rates via a Swan-Ganz-catheter placed within the pulmonary artery, right ventricle, or right atrium in dogs, possibly due to its small inner diameter. In our study, aspiration catheters had similar and high flow rates, approximately 10 times greater than that of a pulmonary artery catheter.…”
Section: Discussioncontrasting
confidence: 75%
“…Studies in dogs and humans have showed that left lateral decubitus positioning may improve survival by allowing air to rise toward the right ventricular apex, thereby relieving the obstruction of pulmonary outflow tract 8,9 . Some authors have attempted to aspirate air from the right ventricle using a PAC with unclear benefit 10,11 . Hyperbaric oxygen may be considered if there are neurological changes evident on physical examination 1 …”
Section: Discussionmentioning
confidence: 99%
“…Evacuation of air from central venous catheter (CVC) is recommended if possible and occasionally up to 50% of entrained air can be removed with proper placement of CVC [55,68]. The optimal position of CVC for aspiration of air is at 2 cm below the junction of right atrium and superior vena cava [55,69]. Fluid resuscitation will increase CVP thereby preventing further entry of gas into the venous circulation [70].…”
Section: Managementmentioning
confidence: 99%